Beliefs about maternal labor supply - Teodora Boneva; Marta Golin; Katja Kaufmann; Christopher Rauh (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
We provide representative evidence on the perceived returns to maternal labor supply. A mother's decision to work is perceived to have sizable impacts on child skills, family outcomes, and the mother's future labor market outcomes. Beliefs about the impact of additional household income can account for some, but not all, of the perceived positive effects. Perceived returns are predictive of labor supply intentions under different policy scenarios related to childcare availability and quality, two factors that are also perceived as important. An information experiment reveals that providing information about benefits of mothers working causally affects labor supply intentions.
Keywords: J22; J13; I26; 330; Subjective expectations; maternal labor supply; childcare; child penalties